Dating Persistent Short-Term Human Activity in a Complex Depositional Environment: Late Prehistoric Occupation at Saruq al-Hadid, Dubai. Issue 4 (23rd May 2019) - Weeks, Lloyd; Cable, Charlotte M; Karacic, Steven; Franke, Kristina A; Price, David M; Newton, Claire; Roberts, James; Al Ali, Yaaqoub Youssef; Boraik, Mansour; Zein, Hassan
ABSTRACT: The archaeological site of Saruq al-Hadid, Dubai, United Arab Emirates, presents a long sequence of persistent temporary human occupation on the northern edge of the Rub' al-Khali desert. The site is located in active dune fields, and evidence for human activity is stratified within a deep sequence of natural dune deposits that reflect complex taphonomic processes of deposition, erosion and reworking. This study presents the results of a program of radiocarbon ( 14 C) and thermoluminescence dating on deposits from Saruq al-Hadid, allied with studies of material remains, which are amalgamated with the results of earlier absolute dating studies provide a robust chronology for the use of the site from the Bronze Age to the Islamic period. The results of the dating program allow the various expressions of human activity at the site—ranging from subsistence activities such as hunting and herding, to multi-community ritual activities and large scale metallurgical extraction—to be better situated chronologically, and thus in relation to current debates regarding the development of late prehistoric and early historic societies in southeastern Arabia.